Traumatic Brain Injury and Olfaction: A Systematic Review - Schofield, Peter W.; Moore, Tammie M.; Gardner, Andrew (Frontiers in Neurology, 2014)
Traumatic brain injury (TBI) is a common condition that is often complicated by neuropsychiatric sequelae that can have major impacts on function and quality of life. An alteration in the sense of smell is recognised as a relatively common complication of TBI, however in clinical practice this complication may not be sought or adequately characterized. We conducted a systematic review of studies concerned with olfactory functioning following TBI. Our predetermined criteria led to the identification of 25 studies published in English which we examined in detail. We have tabulated the data from these studies in 8 separate tables, beginning with Table 1 which highlights each study’s key findings, and we provide a summary/synthesis of the findings in the accompanying results and discussion sections. Despite widely differing methodologies, the studies attest to a high frequency of post-TBI olfactory dysfunction and indicate that its presence can serve as a potential marker of additional structural or functional morbidities.